RESPONS PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS TANAMAN JAGUNG (Zea mays L.) TERHADAP PEMBERIAN PUPUK P DAN K - Fredrik Dynata Simanungkalit; Mbue Kata Bangun; Isman Nuriadi (Universitas Sumatera Utara, 2014)
Using of Central Composite Rotatable Design (CCRD) to determine the surface response producewas not researched yet, so the research have been conducted in UPT BBI Tanjung Selamat, Regencyof Deli Serdang, Province of North Sumatra with the land height ± 25 m above sea level, at May2012 - August 2012 using randomized block design with two factors : two varieties (Bisma and SHS-4) and Fertilizer (P and K with the dose determined from CCRD). Parameters measured were plantheight, number of leaf, time of flower initiation, harvesting age, cob length, number of leaf abovecob, cob diameter, weight of 100 seeds, seed filling rate and dry seeds production. The resultsshowed that the varieties were significantly diffrent to plant height, number of leafs, harvesting age,cob diameter, weight of 100 seeds, the seed filling rate, and dry seeds production. Fertilizer weresigificantly effects to plant height, number of leafs, and dry seeds production. Interaction betweenvarieties and fertilizer were significantly effects to plant height, cob diameter, and dry seedsproduction.Keywords : maize, P fertilizer, K fertilizer, varieties, CCRD